Economic Impact of Consumer Determinants on Household Energy Use: Evidence from Kazakhstan - Kaliyeva, Assem; Turarov, Dauren; Ristić, Lela; Salibekova, Perizat; Zholdasbek, Gani (International Journal of Energy Economics and Policy, 2026)
The quality and productivity of human capital are influenced by household consumption factors, such as spending on health care, education, and better living conditions. Households support the reproduction of the labor force as the main factor of production and invest in the development of human capital through the consumption of goods and services. As technology advances and smart homes emerge, and as demand for services and goods increases, household energy consumption is also increasing. The aim of the study is to assess the economic impact of consumer determinants on household energy consumption. The study used the following indicators: Consumer price index of Housing services and other fuels, Real money income index of population, Annual inflation rate, Percentage of internet users, Employment rate. To assess the impact of factors on the level of household final energy consumption in Kazakhstan using the ARDL model, data covering 2001-2024 were obtained from the National Bureau of Statistics of the Republic of Kazakhstan and the official website of the World Bank. The findings indicated that the Consumer price index of housing services and other fuels has no effect on the Households final energy consumption (1000 t o.e.) component in either the long or short run. Whereas real money income, inflation rate, internet users have a positive influence in both the long and short run, employment rate has a negative effect in both the long and short run.